An Analysis of district Karnal‟s Self - Help Groups‟ & Microfinance Contribution to Women‟s Empowerment: Examining the Impact of Self-Help Groups and Microfinance on Women's Empowerment in Karnal district, Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Women's empowerment refers to the process through which women actively promote their ownwell-being by challenging traditional cultural norms and values. Women's involvement in Self HelpGroups (SHGs) significantly boosted their economic and social independence. This research projectfocuses on the ways in which self-help groups have helped to advance women in Haryana's Karnaldistrict. Both primary and secondary data were gathered to complete the study. The samples wereselected at random using many stages. The findings were analysed statistically, using mean andpercentage, so conclusions could be drawn. The motivations for participating in the Self-help group wereidentified using the Garret ranking method. In order to quantify and analyse the interdependencies of theobserved variables, factor analysis was conducted. The study found that SHGs have a positive effect onthe recipients' economic well-being and social well-being.